Business Architecture Planning in Telkom Penajam Plasa - Masnunah, Siti; Leander Hadisaputro, Elvin (Devotion : Journal of Research and Community Service, 2022)
Plasa Telkom Penajam is an outlet or place of service belonging to PT. Telekomunikasi Indonesia, Tbk (Telkom) which is fully managed by TELKOM and or in collaboration with PARTNER, provided to serve customers, prospective customers, users of Telkom services and or TELKOM Group services who wish to be served online. directly (face to face) with various possible backgrounds or causes, both regarding the need for all information related to Telkom's products and services, as well as to fulfill basic needs themselves. From its business processes, Plasa Telkom Penajam has several problems that have the potential to disrupt its business activities, one of the problems is the occurrence of errors in the management of outgoing modem data and frequent errors in recording, due to the absence of an integrated information system to support activities within the company. In designing the EA at Plasa Telkom Penajam using The Open Group Architecture Framework (TOGAF) and the Architecture Development Method (ADM) which have been limited and consist of several stages, namely the preliminary phase, architectural vision and business architecture. This study aims to identify business processes and create IS/IT blueprints. The result of this research is the design of Enterprise Architecture in order to support its business processes and build an information system to meet the needs of business strategy activities that produce the main blueprints of TOGAF, namely business architecture and application architecture.